Age as a Differential Factor of the Activity of Disabled People in the Rural Areas of the Lubelskie Voivodship - Wiesław Romanowicz; Józef Bergier; Dorota Tomczyszyn (Barometr Regionalny)
The authors present financial aspects of the lives of the disabled living in the Lubelskie Voivodship in the context of age. All the data included are a result of empirical studies conducted in the rural areas. From the presented findings it ensues that the younger the age category of the respondents, the stronger the sense of the material wealth and higher economic status. The above attitudes are a result of better adaptation of the youth to the realities of everyday life and diversified sources of income. Taking this into consideration, it needs to be said that despite major economic problems the rural disabled face, we can observe systematic change in the awareness of this social group.